Soft tissue sarcomas: recommendations - Novak, Marko; Turnšek, Nina; Unk, Mojca; Žagar, Tina; Blatnik, Olga; Kramer, Sonja; Skoblar Vidmar, Marija; Perhavec, Andraž; Vivod, Gregor; Blatnik, Ana; Kogovšek, Katja; Novosel, Tilen; et al. (Onkologija : Slovenian Journal of Oncology, 2026)
Recommendations for the management and treatment of patients with soft tissue sarcoma emphasize the importance of individualized treatment in a referral center with a multidisciplinary sarcoma team. The only referral sarcoma center in Slovenia is the Institute of Oncology Ljubljana. Key components include imaging diagnostics using MRI and CT scans and a core needle biopsy. Surgical treatment remains the cornerstone of therapy, while radiotherapy reduces the risk of local recurrence. Systemic treatment with chemotherapy or targeted drugs is primarily considered for advanced, metastatic disease. The 2026 recommendations are available at the Institute of Oncology Ljubljana website.